Insect mitochondria as targets of freezing-induced injury - Štětina, T; Des Marteaux, L E; Koštál, V (Proceedings. Biological sciences, 2020)
Many insects survive internal freezing, but the great complexity of freezing stress hinders progress in understanding the ultimate nature of freezing-induced injury. Here, we use larvae of the drosophilid fly, Chymomyza costata to assess the role of mitochondrial responses to freezing stress. Respiration analysis revealed that fat body mitochondria of the freeze-sensitive (non-diapause) phenotype significantly decrease oxygen consumption upon lethal freezing stress, while mitochondria of the freeze-tolerant (diapausing, cold-acclimated) phenotype do not lose respiratory capacity upon the same stress. Using transmission electron microscopy, we show that fat body and hindgut mitochondria swell, and occasionally burst, upon exposure of the freeze-sensitive phenotype to lethal freezing stress. By contrast, mitochondrial swelling is not observed in the freeze-tolerant phenotype exposed to the same stress. We hypothesize that mitochondrial swelling results from permeability transition of the inner mitochondrial membrane and loss of its barrier function, which causes osmotic influx of cytosolic water into the matrix. We therefore suggest that the phenotypic transition to diapause and cold acclimation could be associated with adaptive changes that include the protection of the inner mitochondrial membrane against permeability transition and subsequent mitochondrial swelling. Accumulation of high concentrations of proline and other cryoprotective substances might be a part of such adaptive changes as we have shown that freezing-induced mitochondrial swelling was abolished by feeding the freeze-sensitive phenotype larvae on a proline-augmented diet.
Keywords: Drosophilidae; zmrazování; larva; Larva; Insecta; hmyz; Mitochondria; insects; mitochondrial morphology; zvířata; mitochondrie; Acclimatization; Freezing; freeze tolerance; aklimatizace; Animals